Pancreas cancer: experience of the last 10 years - Viola Alles, Alberto (Cirugía del Uruguay, 1979)
142 pancreatic cancers were diagnosed in the period 1966 - 76 in the Hospital de Clinicas (University Hospital) and Oncological Institute.